ARTISTIC AND MYSTICAL INTERPRETATION OF THE IDEAS OF THE SURAH "AT-TARIQ" IN THE GAZEL OF ALISHER NAVA’I "PROMISING TO COME LAST NIGHT..." - Shermatova, Umida Sapaevna (SCIENCE and SOCIETY, 2026)
This article analyzes Alisher Navoi’s ghazal "Having Promised to Come Last Night..." with the Surah At-Tariq of the Holy Quran using a comparative-typological and hermeneutic approach. The Quranic and mystical essence of the ghazal’s motifs of night, wakefulness, expectation, hijran, light, and farewell are revealed. The poet’s mastery in artistically depicting the human soul’s striving for Truth and the path to spiritual perfection through romantic experiences is emphasized. The results of the analysis demonstrate that Quranic ideas are expressed in Navoi’s ghazal not directly, but through mystical and artistic thought.